ANALYSIS OF THE CONTRIBUTION OF TAWHID LEARNING TO IMPROVING SELF-CONTROL AND THE FACTORS CAUSING THE MORAL DECADENCE OF STUDENTS IN PESANTREN - Bagus Sugiharto; Fatahillah Arrozi; Agusyanto Agusyanto; Diah Ayu Cristi Allfian (International Conference on Humanity Education and Society (ICHES), 2023)
The decline in morals that is rife, moves researchers to study what things are reinforcing self-control and the factors that cause weak self-control. After making observations the researchers made a hypothesis, that learning monotheism can increase one's self-control. To test the truth of this hypothesis, a study was carried out with the aim of obtaining empirical data regarding the relationship between monotheism learning and self-control. By using the quantitative calculation method, it was found that research results revealed that religiosity, in this case, is devoted again to the study of monotheism. became one of the factors that led to increased self-control with a contribution of 21% with r = 0.428. The results of this study indicate that the position of monotheism learning in increasing self-control has a contribution of 21.4% and is included in the low category. These results raise further questions about what factors are the reasons so that students are weak or lacking in terms of managing their self-control, causing moral decadence in the Islamic boarding school. By using a qualitative approach method, in-depth interviews were conducted with teenage students, namely 15-17 years old. From the results of the interviews it was concluded that there were several factors that caused students to violate, namely; (1) Lack of fear of Allah, (2) Lack of teacher professionalism, (3) Crowded daily activities, and (4) Loosening of rules.